Fostering humanization in education: a scoping review on mindfulness and teacher education - Soares, Filipa; Lopes, Amélia; Serrão, Carla; Ferreira, Elisabete (Frontiers in Education, 2024)
The humanization of education is increasingly invoked as a counterpoint to the overly technical and instrumental view of education that has developed in recent decades. In this article it is intended to contribute to identify ways towards education humanization through teacher education. As the research on humanization of education at the empirical level remains vague, studies on mindfulness in teacher education are taken as a first means of operationalising research into the conditions of fostering reflection on the humanization of education in teacher education. As a step along this path a scoping review was conducted to map research on mindfulness in teacher education and its relationship with the humanization of education, guided by questions such as how MBAs have been conceptualized and their role in humanizing teacher education.The scoping review allowed the identification of 21 articles which were charted according to analytical frameworks regarding: the mindfulness conceptualization, chosen research paradigms, and the role given to mindfulness in teacher education. Findings suggest that the way mindfulness is conceptualized in research makes an essential difference in acknowledging its instrumental and/or transformative role in education. Transformative approaches may bring an added educational value, addressing the subjective, reflective, and critical dimensions of teacher education. From this point of view, mindfulness-based education practices could be a promising pathway to inform empirical research on the humanization of education through teacher education.